Pengetahuan dan Peran Orang Tua terhadap Prestasi Belajar Anak Autis di Sekolah Anak Berkebutuhan Khusus Unggul Sakti Jambi - Rasyidah azhari Azhari; Exsos Grend Dais; Noprival Noprival (Riset Informasi Kesehatan, 2018)
Abstract Background : The problems faced by parents in increasing achievement of students with autism was lack of parents knowledge and role of parents in facilitating process of learning at home. In this case, knowledge and the role of parents is really needed in improving their achievement in SABK Unggul Sakti Jambi. Method : This study is a quantitative research with cross sectional design that aims to determine the correlation of knowledge and role of parents toward students’ achievement at SABK Unggul Sakti Jambi. The samples used were 30 parents. Total Sampling was used in this study. There were 30 parents of students with autism as the sample. Data were collected through questionnaire and checklist sheet. Data were processed by univariate and bivariate Spearman Correlation Test. Results : The results of univariat analysis showed that 73.3% students had a moderate learning achievement, another finding revealed that 60% of student were categorized low achievement. Also, 63.3% of respondents unsatisfiend role in facilitating students to increase their achievement. Then, bivariate analysis indicated that there was a significant correlation between knowledge (p-value=0.017) and role of students (p-value=0.000) toward the learning achievement. Conclusion : It is expected to the school to continue the efforts to increase knowledge and the role of parents in increasing achievement of students with autism to do a good cooperation. Furthermore, the role of their parents extremely has impact towards learning process of students both at school and home. Keyword : Autistic Child, Achievement, Knowledge, Role